Ekwiwalenty rosyjskiej nazwy własnej Kołobok w języku polskim - Orzechowska, Joanna (Acta Polono-Ruthenica, 2019)
The paper presents an analysis of Polish equivalents of the Russian proper name Kolobok. Their diversity results from insufficient familiarity with the Russian source text (a folk fairy tale) in Poland, which is caused by little acquaintance with the hero of the story and lack of a Polish equivalent of such a fairy tale character that carries the same communicative value. Examples in-cluded in the paper do not always preserve the communicative value of the context: in few cases, it had been assessed which elements of the meaning are relevant and significant, and which are redundant, i.e. semantically irrelevant. Provisional equivalents in most cases are based on the inner semantics of the discussed proper name.